Contribution of Education Policy Reforms Towards Gender Dynamics and the Formalization of Domestic-work Sector: A Case of Mafinga Town Council, Tanzania - Kiwonde , Flora M; Kyando, Newton M. (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2022)
Currently, Tanzania is experiencing the policy of free education up to secondary school level. On the other hand, in Tanzania, domestic work is one of the sectors with the highest share of informal employment. However, after the introduction of free education policy up to form four, the availability of domestic workers has became somehow difficult whereas the formalization of the domestic sector has also gained paceThis background has been a bench-mark to this study that analysed the influence of the current educational policy towards the formalization of domestic sector in Mafinga Town. The study was qualitative in nature whereby the interview of 30 domestic workers, 10 employers and 5 individuals from workers’ union was conducted. The study found out that the new education policy has contributed towards the increase of the age to domestic sector from 12 years to 17 years, the number of daily routine workers has increased as opposed to residential workers, domestic works involved both males and females, there was the increase of the middle men to facilitate the availability of domestic workers. Due to increased awareness, domestic workers were demanding their rights including the vacation from their employers and better salaries. In addition, there had been scarcity of domestic workers that has led to the mushrooming of day care centers. Needless to say, domestic workers faced unlimited number of challenges including overworking with low wages, delayed payments, harsh working climates as well as low social recognition. The study hereby recommended for the improvement in the education sector in favor of females. That would relieve domestic workers from the involvement in the informal sectors such as domestic sectors.